Sequence analysis of the Malaysian low pathogenic avian influenza virus strain H5N2 from duck - Ahmad Rizal, Fatin; Kok, Lian Ho; Omar, Abdul Rahman; Wen, Siang Tan; Mariatulqabtiah, Abdul Razak; Iqbal, Munir (Multidisciplinary Digital Publishing Institute, 2023)
The avian influenza viruses (AIV) of the H5 subtype have the ability to mutate from low pathogenic (LPAI) to highly pathogenic (HPAI), which can cause high mortality in poultry. Little is known about the pathogenic switching apart from the mutations at the haemagglutinin cleavage site, which significantly contributes to the virus virulence switching phenomenon. Therefore, this study aimed to compare the molecular markers in the haemagglutinin (HA), neuraminidase (NA), and matrix (M) genes of a locally isolated LPAI AIV strain H5N2 from Malaysia with the reference HPAI strains using bioinformatics approaches, emphasising the pathogenic properties of the viral genes. First, the H5N2 strain A/Duck/Malaysia/8443/2004 was propagated in SPF eggs. The viral presence was verified by haemagglutination assay, RT-PCR, and sequencing. Results showed successful amplifications of HA (1695 bp), NA (1410 bp), and M (1019 bp) genes. The genes were sequenced and the deduced amino acid sequences were analysed computationally using MEGA 11 and NetNGlyc software. Analysis of the HA protein showed the absence of the polybasic cleavage motif, but presence of two amino acid residues that are known to affect pathogenicity. There were also two glycosylation sites (glycosites) compared to the reference HPAI viruses, which had three or more at the HA globular head domain. No NA stalk deletion was detected but the haemadsorbing and active centres of the studied NA protein were relatively similar to the reference HPAI H5N2 isolates of duck but not chicken origins. Six NA glycosites were also identified. Finally, we observed a consistent M1 and M2 amino acid sequences between our LPAI isolate with the other HPAI H5N1 or H5N2 reference proteins. These data demonstrate distinct characteristics of the Malaysian LPAI H5N2, compared to HPAI H5N2 or H5N1 from ducks or chickens, potentially aiding the epidemiological research on genetic dynamics of circulating AIV in poultry.